Repeated hyperstimulation affects the ultrastructure of mouse fallopian tube epithelium - Sevastiani ANTONOULI; Maria Grazia PALMERINI; Serena BIANCHI; Gianna ROSSI; Sandra CECCONI; Manuel BELLI; Sara BERNARDI; Mohammad Ali KHALILI; Giuseppe FAMILIARI; Stefania Annarita NOTTOLA; Guido MACCHIARELLI (The Society for Reproduction and Development, 2020)
Controlled ovarian hyperstimulation (COH) is routinary used in assisted reproductive technologies (ARTs) to increase the yields of mature oocytes. The possibility that patients with a history of failures or poor-responders may develop side-effects following these treatments is still debated. Epidemiological studies reported controversial results about pregnancy outcome and the risk of developing gynecological cancers. By using a mouse model, here we compared the ultrastructural features of fallopian tubes (FTs) obtained from mice undergoing or not (control, CTR) four (4R) and eight (8R) rounds of gonadotropin stimulation. Although the morphological characteristics of oviductal layers seemed unaffected by repeated treatments, dose-response ultrastructural alterations in the ampulla appeared in the 4R group and even more in the 8R group. The targets were oviductal ciliated (CCs) and non-ciliated (NCCs) cells, which showed damaged mitochondria and glycogen accumulations in the cytoplasm. The drastic reduction of CCs, evident after 4R, was supported by the absence of cilia. After 8R, glycogen granules were significantly reduced and massive degeneration of mitochondria, which appeared swollen and/or vacuolated, occurred in NCCs. Moreover, disintegrated mitochondria were found at the periphery of mitophagic vacuoles with evident signs of cristolysis. The morphometric analysis evidenced a significant increase in the density and frequency of damaged mitochondria after 4R and 8R. The absence of cilia, necessary to sustain oviductal transport of oocytes, spermatozoa and embryos, may originate from either mitochondrial dysfunction or glycogen consumption. These results suggest that repeated COH treatments could induce alterations impairing fertilization and embryo transport toward the uterus.